Dynamics of Meta Governance in the Proactive Recruitment Process f Prospective Members Ofo the Republic Of Indonesia Police - Samad, Fadly; Thahir Haning, Muh.; Ibrahim, Muh. Akmal (Journal of Neonatal Surgery, 2025)
This research aims to analyze the dynamics of meta-governance in the proactive recruitment process for prospective members of the Indonesian National Police in terms of initial conditions and meta-governance elements in collaborative innovation. The research design used was qualitative with a case study strategy. This research was carried out at 3 Regional Police Forces (POLDA), namely South Sulawesi Police, North Kalimantan Police, and Papua Police. Determination of research informants using purposive sampling, where informants are selected based on involvement and knowledge. Data collection includes observation, in-depth interviews, and document review. Data analysis techniques use interactive data analysis. Validity and reliability using triangulation, namely combine various data sources, methods, or theories to verify and strengthen research findings. Research results regarding initial conditions in the proactive recruitment program for prospective members Polri show that the Polri institution has long built cooperation with stakeholders on other recruitment channels before engaging in a proactive recruitment program, so it is not difficult to initiate cooperation in proactive recruitment. Element Metagovernance in the proactive recruitment program for prospective members of the National Police shows that The rules of the game and implementation of SOPs refer to the regulations of the National Police Chief and Jukrah. Furthermore, the rules of the game and SOP are discussed in uniformity of perception, briefing, discussion, and coordination between the Regional Police and all the stakeholders